DAMPAK PENURUNAN PRODUKSI UDANG TERHADAP PEM BENIHAN (HATCHERY) UDANG WINDU DI SULAWESI SELATAN - Nur Ansari Rangka (Berkala Perikanan Terubuk, 2012)
Fry requirement to embank one is at Indonesia as much ± 11 Billion / years withassuming that diffusion average for every ranging hectare among 2.000 – 3.000fries / Ha / M.T. Fry haul of salt water varying bases season, ranging 500 800million number. fry / yr, so can't expect to meet the need fishpond farmer.hatchery's production exhaustive Indonesia, just can supply 16,6 % of farmerneed. Far ranging productive fishpond at south Sulawesi ± 64.000 ha with fry theneed ± 600 million, number / yrs. (2 MT /'S times Yrs.s), gotten from hatchery'sproduction that is at South Sulawesi and south Sulawesi extern, and the capturerfry of nature. Fry requirement embanks at South Sulawesi to be accomplished43,42 %, Fries lacking picture shrimp that needed will the greater if diffusion beincreased By Problem fry procurement to embank at South Sulawesi to experiencedilemma among farmer embanks at one hatchery's party and entrepreneur inopposition. Farmer embanks to perceive fry lack at stated periods, hatchery'sentrepreneur on the contrary excess fry did not even saleable absolutely at statedperiods. This research aims to know operational system problem hatchery who isat South Sulawesi.